(untitled) (Світ фінансів, 2017)
Дишкант М. В., Дишкант О. В. До питання управління інтелектуальною власністю. Розглянуто проблеми управління інноваційною діяльністю та інтелектуальною власністю.Розкрито роль національної інноваційної сфери у формуванні конкурентних переваг національної економіки. Окреслено основні проблеми та диспропорції у політиці фінансування наукових досліджень та інноваційно-інвестиційної діяльності. Dyshkant M., Dyshkant O. To the question of intellectual property management. The problems of management by innovative activity and intellectual property are considered. The role of national innovative sphere is exposed in forming of competitive edges of national economy. Basic problems and disproportions are outlined in the policy of financing of scientific researches and innovative-investment activity.